A Model of Dendritic Cell Therapy for Melanoma - Radunskaya, Ami; de Pillis, Lisette; Gallegos, Angela (Frontiers in Oncology, 2013)
Dendritic cells are a promising immunotherapy tool for boosting an individual's antigen specific immune response to cancer. We develop a mathematical model using differential and delay-differential equations to describe the interactions between dendritic cells, effector-immune cells and tumor cells. We account for the trafficking of immune cells between lymph, blood, and tumor compartments. Our model reflects experimental results both for dendritic-cell trafficking and for immune suppression of tumor growth in mice. In addition, in silico experiments suggest more effective immunotherapy treatment protocols can be achieved by modifying dose location and schedule. A sensitivity analysis of the model reveals which patient-specific parameters have the greatest impact on treatment efficacy.